2018
DOI: 10.1093/cid/ciy503
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Follow-up of Middle East Respiratory Syndrome Coronavirus Cases and Contacts—Abu Dhabi, United Arab Emirates

Abstract: Transmission of MERS-CoV was not documented in this investigation of mostly asymptomatic and mildly symptomatic cases and their household contacts. These results have implications for clinical management of cases and formulation of isolation policies to reduce the risk of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…A similar situation was observed in Saudi Arabia, where up to 50% of MERS-CoV cases were classified as secondary, due to possible human-to-human transmission through contact with asymptomatic or symptomatic individuals infected with MERS-CoV [42]. Furthermore, limited human-to-human transmission of MERS-CoV was observed in several other clusters in other countries, including family members [14][15][16][17][18][19] and patients in health care facilities [39,40,[42][43][44].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A similar situation was observed in Saudi Arabia, where up to 50% of MERS-CoV cases were classified as secondary, due to possible human-to-human transmission through contact with asymptomatic or symptomatic individuals infected with MERS-CoV [42]. Furthermore, limited human-to-human transmission of MERS-CoV was observed in several other clusters in other countries, including family members [14][15][16][17][18][19] and patients in health care facilities [39,40,[42][43][44].…”
Section: Discussionsupporting
confidence: 62%
“…Limited human-to-human transmission of MERS-CoV has been described mostly in health care setting [2,[6][7][8][9][10][11][12][13] and small household clusters of community-acquired cases, including a family cluster of mild disease [14][15][16][17][18][19]. Larger outbreaks have been reported in healthcare settings, which have led to multiple chains of limited transmission, as a result of contact with index cases or inadequate infection prevention and control measures causing excessive morbidity and mortality in several countries [2,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…More severe cases were also found to have slower responses 28,30 ; 75% of patients who died had not seroconverted by week 3 28 . Some authors have hypothesized 54,55 that seroconversion rates in severe cases may be associated with prolonged viral shedding, and that low antibody responses in mild cases may be due to short-lived infections. Another study 46 suggested that weaker antibody responses to endemic HCoVs (specifically HCoV-229E) might be because these mainly infect the upper respiratory tract.…”
Section: Hcov-hku1mentioning
confidence: 99%
“…To compare SARS-CoV-2 SARs with other viruses, we reviewed articles describing household secondary transmission of SARS-CoV, Middle East Respiratory Syndrome coronavirus (MERS-CoV), and other coronaviruses. We found seven articles reporting household SARs of MERS-CoV, 61 67 six of SARS-CoV, 68 – 73 and four of other coronaviruses ( S3 Table ). 74 77 …”
Section: Comparison With Other Virusesmentioning
confidence: 99%